Breaking the ‘change of scale’ stalemate - Caron, Patrick (Perspective, 2025)
Version française de l'article Looking for large-scale impact is a legitimate ambition of policymakers and funding agencies; this calls for moving beyond the local impact of innovations and development projects designed to transform food systems. Yet, experience over the past 30 years has shown that impact at scale does not always live up to expectations. It reveals how intermediate territorial levels matter to link local innovation and solutions to global challenges. The intermediate level is either not thought about at all, or poorly thought through; it is the missing link where the ‘contamination’ or spread of ideas and ‘bricolage’ take place, where cobbling together of territory-based solutions is designed and implemented. This is the only way to ensure that innovations are consistent with development challenges and have an impact at scale.